Formation of stereocomplex in enantiomeric poly(lactide)s via recrystallization of homocrystals: An in-situ X-ray scattering study. (September 2016) - Yin, Yongai; Liu, Guoming; Song, Yan; Zhang, Xiuqin; de Vos, Sicco; Wang, Ruyin; Joziasse, Cornelis A.P.; Wang, Dujin
Graphical abstract: Highlights: SC formation in PLLA/PDLA was investigated by in-situ WAXS and SAXS. Formation of SC depended strongly on annealing temperature. A new concept of "diffusion zone" was proposed to explain the results. Abstract: The formation of stereocomplex (SC) in enantiomeric poly(lactide)s via recrystallization of homocrystals was investigated by using simultaneous wide-angle and small-angle X-ray scattering. When the symmetric blend of poly(l -lactide) (PLLA) and poly(d -lactide) (PDLA) was heated from the glassy state at a slow heating rate (5 °C/min), predominant homocrystals were formed during heating (cold crystallization). Melting of homocrystals and crystallization of stereocomplex occurred almost simultaneously. In this case, the diffusion of PLLA and PDLA chains played an important role in determining the maximum attainable SC crystallinity. The crystallization behavior during annealing at different temperatures (185 °C, 195 °C and 225 °C) and subsequent cooling was further investigated to understand the effectiveness of annealing on the formation of stereocomplex. The stereocomplex content was unchanged during annealing at 185 °C and kept constant during cooling to room temperature. The SC crystallinity increased slightly during annealing at 195 °C and subsequently cooling. On the other hand, the content of SC increased during annealing at 225 °C and increased remarkably during cooling. A possible mechanism considering the diffusion of PLLA and PDLA chains was proposed.